Genetics and Epigenetics of Parkinson's Disease - Fabio Coppedè (The Scientific World Journal)
In 1997 a mutation in the a-synuclein (SNCA) gene was associated with familial autosomal dominant Parkinson’s disease (PD). Since then, several loci (PARK1-15) and genes have been linked to familial forms of the disease. There is now sufficient evidence that six of the so far identified genes at PARK loci (a-synuclein, leucine-rich repeat kinase 2, parkin, PTEN-induced putative kinase 1, DJ-1, and ATP13A2) cause inherited forms of typical PD or parkinsonian syndromes. Other genes at non-PARK loci (MAPT, SCA1, SCA2, spatacsin, POLG1) cause syndromes with parkinsonism as one of the symptoms. The majority of PD cases are however sporadic “idiopathic” forms, and the recent application of genome-wide screening revealed almost 20 genes that might contribute to disease risk. In addition, increasing evidence suggests that epigenetic mechanisms, such as DNA methylation, histone modifications, and small RNA-mediated mechanisms, could regulate the expression of PD-related genes.